Numerical investigation on erosion wear and strength of main gas pipelines bends - Doroshenko, Ya.V.; Kogut G.М.; Rybitskyi, I.V.; Tarayevs'kyy, O.S.; Pyrig, T.Yu. (Physics and Chemistry of Solid State, 2021)
The purpose of this work is to ensuring the strength of main gas pipelines bends by studying the peculiarities of single-phase and multiphase flows movement through the internal cavity, the processes of erosion wear and the wall stress state. The problem of synergistic influence of gas-dynamic processes (uneven pressure distribution in the internal cavity), temperature difference and erosion wear on the stress state of the bends of main gas pipelines was solved by numerical simulation. Based on the results of simulation the processes of bends erosion wear, an algorithm for three-dimensional simulation of bend walls erosion defects was developed. The complex three-dimensional geometric shape of the erosion defects of the bend wall varied according to the rate of erosion wear process. This algorithm made it possible to determine the regularities for the influence of the bend erosion defects magnitude on bends stress state. It was established that considering the maximum depth of bend erosion defects 9.6 mm, 10.5 mm and 11.9 mm, the equivalent stresses in the deepest places of the erosion defect were greater than on the concave side of the bend and in straight sections of the pipeline.